Legal Compliance and Enforcement Against Gambling Crimes in Sorong City - Dimas Bayu Erlangga (Fakultas Hukum Universitas Muhammadiyah Sorong, 2025)
This study aims to analyze the role of law enforcement against perpetrators of gambling crimes and the efforts that can be made to combat gambling practices in Sorong City. The method used in this study is sociological or empirical legal research, which views law as behavior that exists within society, not merely as legal norms. The study reveals that gambling has negative impacts that harm the morality and mentality of society, particularly among the younger generation. The novelty of this research lies in its in-depth analysis of the need for cross-sectoral cooperation and the utilization of information technology in law enforcement in the digital age. The results of the study indicate that law enforcement against gambling in Indonesia requires an effective, fair, and sustainable system, as well as the need for specific regulations such as Law No. 7 of 1974 on Gambling Control and Government Regulation No. 9 of 1981. This study concludes that to combat gambling-related crimes, an approach involving inter-sectoral collaboration, increased public legal awareness, and the application of advanced information technology is needed to support more effective and efficient law enforcement.